Youth Constructions of the Future: Depictions of and Responses to AI on Scratch (Constructionism Conference Proceedings, 2025)
This study examines how youth engage with AI through Scratch projects, revealing how they depict, critique, and reimagine futures with AI. By analyzing 131 projects and 22,692 comments, we identified five representations of AI: Game Player, Conversational Agent, Learning Entity, Discussion Topic, and Creative Partner. Youth creators and commenters actively negotiate AI’s meaning, envisioning futures where AI is playful, collaborative, or dystopian. Findings highlight the importance of constructionist learning environments for youths’ collaborative sensemaking regarding emergent technology.